Pengaruh Penanaman Modal Asing, Indeks Persepsi Korupsi, Kemiskinan, Pengangguran dan Upah Minimum Terhadap Ketimpangan Pendapatan Di Indonesia - Karimi, Kasman; Mulyani, Pertiwi; Murialti, Neng; Tibrani, Tibrani (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2023)
This study aims to analyze the influence directly or indirectly of Foreign Investment, Corruption Perception Index, Poverty, Unemployment and Minimum Wage on Income Inequality in Indonesia. The data used in this study is a secondary type of data sourced from the offices of the Central Statistics Agency, the World Bank Web and Transparency International. The data analysis method used is Multiple Linear Regression data (time series) in Indonesia for 25 years from 1997 to 2021. Based on the results of the analysis, it is known that Foreign Investment, Corruption Perception Index, Poverty, Unemployment, and Minimum Wage have a significant effect on Income Inequality in Indonesia.